Tiny, yet sufficient: 25 % of capacity retention increase with NCM811 cathode realized by 1.5 % of block copolymer modification - Liu, Xingchen; Xu, Xiaobo; Li, Jiapei; Yang, Ming; Xu, Yutao; Zhu, Jin; Chen, Jing; Cheng, Ya-Jun; Gao, Yanfeng; Xia, Yonggao (Journal of energy storage, 2024)
Nickel-rich layered materials (LiNi0.8Co0.1Mn0.1O2, NCM811) are subject to electrochemical performance degradation and structural damage at high voltage. A new concept is proposed in this work using a multi-functional block copolymer of poly (urethane)-block-poly (dimethyl siloxane) (PUDMS) to modify the NCM811 particle surface and improve the high voltage electrochemical performance. The near NCM811 particle surface solvation structure of the electrolyte is tuned by the PU block to suppress electrolyte solvent decomposition and promote the formation of an electrochemically stable CEI layer. The HF attack is inhibited by the PDMS block resulting in reduced transition metal dissolution and retarded structure degradation. With the PUDMS modification, the capacity retention of the half-cell with the NCM811 cathode is significantly improved (63.6 % vs. 75.9 % after 200 cycles, 1C, 2.8–4.5 V). The cyclic stability of the NCM811||graphite is enhanced with the capacity retention increased from 63.7 % to 80.2 % (0.5C, 2.8–4.5 V). [Display omitted] •A new multi-functional block copolymer of PU and PDMS is used to modify NCM811.•Near surface lithium-ion solvation structure is manipulated by PUDMS.•HF is scavenged by PUDMS to stabilize NCM811 cathode structure.•Full cell electrochemical performance is improved with PUDMS modification.